Pattern of Carbapeneme Resistance Among Bacterial Population in various Water Bodies of Delhi/NCR - NAMITA BEDI,; ARPIT BANSAL,; RAJNI GIAND, (International Journal of Pharma and Bio Sciences, 2017)
Current investigation was aimed to enhance the knowledge about the prevalence of antibiotic resistance in diverse bacterial genera of varied water bodies of Delhi and NCR. During the period of August to November 2012, samples were collected from various water sources (RO water, tap water, stagnant water, river water and sewage treatment plant water). The most prevalent bacteria were Enterobacter aerogens (34.37%) from drinking water, Klebsiella (69.23%) from stagnant water, E.aerogens (23.52%) from river water and Klebsiella (20%) and Citrobacter diversus (20%) from sewage treatment plant water. Antimicrobial susceptibility of bacterial isolates was evaluated against 7 antibiotics using Kirby-Bauer disk diffusion method. The highest rate of resistance was observed with carbapeneme (48.38%), Cephalosporin (30.64%) Quinolones (17.74%) and aminoglycosides(3.2%) antibiotics respectively .Carbapenem resistance were detected in 3 isolates of E.coli and Pseudomonas respectively ,and 1 isolate of Klebsiella.